Pengembangan Model Pembelajaran Senam Healty Fun Untuk Anak SLB di Kota Magelang - Anggitasari, Bernadeta Yovina; Hartono, Mugiyo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The purpose of research is to produce healty Gymnastics Instructional Model Development Fun, Grade V and VI in SLB-C Magelang City. This research is the development of the procedures of product development; (1) analysis, (2) develop initial product form, (3) expert validation test, (4) the first product revision, the revision of the product based on the evaluation of experts and trial I (20 students). Revised used for improvements to the initial product, (5) the trial II (30 students), (6) the revision of the final product is done based on the results of the field trials, (7) the results of a late model gymnastics healty fun for students of classes V and VI which is generated through the revision II trial. Based on the results of research trials I obtained a percentage of 87% (good), the expert evaluation is obtained percentage of 89% (good). II trial research results obtained by the percentage of 96% (excellent). From the trial I and II, there was an increase by a margin of 7%. It can be concluded that the development of gymnastics healty fun learning model can be used as an alternative to teachers provide learning materials rhythmic gymnastics penjasorkes particularly good for classes V and VI SLB-C in Magelang and gymnastic activities that teachers do on a regular basis.